GOVERNMENT PARTNERS: STUDI HUBUNGAN ULAMA DAN PEMERINTAH DALAM PEMBANGUNAN KOTA TASIKMALAYA, JAWA BARAT - Maulana Janah (Jurnal Analisa Sosiologi, 2024)
This research aims to describe the strategic position of Ulama in the system and structure of society having changes due to development. This position is directly proportional to the diverse responses to regional development issues in Tasikmalaya. The next goal is to explain the position of Ulama as partners, mediators, actors, and motivators of work ethic development in Tasikmalaya government. This research employs a qualitative method with an inductive approach. Data collection techniques are through observation, interviews, and documentation studies. The data processing is carried out by means of reduction, display, and verification. They have been classified and categorized so that they can be presented properly. As a framework and analysis, the theory used in this research is Geertz's theory, namely Ulama as cultural brokers combined with Horikoshi's theory, namely political entrepreneurs. The results prove that they are positioned as political mediators and regional development involved in policy formulation and local regulation making. Ulama as a symbol of religious authority and legitimacy, their involvement can be seen in responding to and providing support for local government policies. Furthermore, they are also positioned as social actors who initiate and are intensely involved in the process of educational development. The development is related to the application of religious values, Ulama as guardians of Islamic tradition and orthodoxy. Finally, they also act as motivators who provide direction and guidance on work ethic. They are independent entrepreneurs. The result of this research makes a theoretical contribution to the development of anthropology and sociology of religion. Practically, it is useful for regional and community development policies.